Selection of Mungbean Genotypes Against Waterlogging Stress (Bangladesh Agronomy Journal, 2023)
A pot experiment was conducted in the vinyl house of Sher-e-Bangla Agricultural University (SAU), Dhaka-1207, during kharif-I season (March to June 2022) to identify waterlog tolerant mungbean genotypes. Thirty mungbean genotypes (29 advanced lines and one variety, BARI Mung-6) were evaluated under waterlogging (96 hours) and normal conditions. Waterlogging caused a drastic reduction in dry matter and seed yield in mungbean, however, genotypes showed variable response to waterlogging. Under waterlog condition the higher relative yield was found in M11, M8, M30, M7, M16 and M14 while lower in M2 and M17. Dry matter production also varied among the genotypes due to waterlogging; however, dry matter production of the genotypes M8, M7, M22, M2, M19 and M11 were comparatively higher than other genotypes. Stress tolerance index (STI), yield index (YI) and relative yield (RY) of M16, M20, M7, M8, M11, M30 and M14 were higher than other genotypes. On the basis of dry matter production, STI, YI and RY, genotypes M7, M8, M11, M12, M16, and M20 could be selected as relatively tolerant genotypes against waterlogging stress. Bangladesh Agron. J. 2023, 26(1): 40-47